Where is the Surgical Education of Obstetrics and Gynecology Residents Headed?. (October 2015) - Ruple, Shawna M.; Forstein, David A.; Barrow, James C.
Abstract : OBJECTIVE: The Accreditation Committee of Graduate Medical Education (ACGME) has provided a minimum threshold for various procedures. The Review Committee specifically states that these cutoffs are not to be used as a surrogate for measuring individual residents' achievement of competency. In light of fewer hysterectomies being performed nationally and recent restrictions placed on resident duty-hours, we predict less resident exposure to hysterectomy cases during their postgraduate training. METHODS: Obstetrics and gynecology residents completing a total of 4 postgraduate years between 2001 and 2011 were eligible to be included in the study. Current Procedural Terminology codes were scanned for hysterectomy codes. These numbers were then compared with the corresponding residents' ACGME case logs for validity. The primary outcome evaluated was the total mean number of hysterectomies performed by graduating residents. Secondary outcomes included the mean number of abdominal, laparoscopic, and vaginal hysterectomies performed by graduating residents. RESULTS: N=46 residents over an 11-year study period. Graduation year, number of residents, and duty hour restrictions (no restriction 2002–2003 compared with restrictions 2004–2011) were possible predictors in bivariate and multivariate analyses. Residents completed an average of 191 (standard deviation [SD] 12.2) hysterectomies in 2001 compared with 81 (SD 10.9) in 2011 ( P <.001). Before duty hour restrictions, residents performed a mean of 218.5 (SD 40.2) hysterectomies compared with a mean of 131.3 (SD 41.9) following implementation of duty hour restrictions ( P <.001). CONCLUSION: In multivariate analysis, graduation year was the only statistically significant and independent predictor of hysterectomy cases completed during obstetrics and gynecology residency.